1994
DOI: 10.1177/088307389400900318
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia Secondary to High Valproate Levels in Children With Epilepsy

Abstract: We reviewed the frequency of valproate-induced thrombocytopenia in children with epilepsy in our institution. Sixty-four (21%) of 306 children taking valproate developed thrombocytopenia. Thirty-two of these 64 patients had at least one platelet count lower than 100 x 10(3)/mm3. Eight patients developed signs of bleeding. Low platelet levels were typically noted in patients with serum valproate levels of over 140 micrograms/mL, and reduction of the medication dose usually resulted in a prompt increase in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 12 publications
9
51
0
5
Order By: Relevance
“…MCV was significantly higher in the study group, whereas HCT, MCH, and MCHC showed no significant differences. As expected, in the study group platelet counts were significantly lower compared to the control group, a well-known side effect of valproic acid treatment, but without reaching clinical importance [15] (Table 2). …”
Section: Resultsmentioning
confidence: 54%
“…MCV was significantly higher in the study group, whereas HCT, MCH, and MCHC showed no significant differences. As expected, in the study group platelet counts were significantly lower compared to the control group, a well-known side effect of valproic acid treatment, but without reaching clinical importance [15] (Table 2). …”
Section: Resultsmentioning
confidence: 54%
“…6,16 In females, the results of our present study shows the percentage of thrombocytopenia is reported 19.04% and in males 9.8%. The underlying mechanism for gender difference in platelets counts is unclear; it could be that the immune system of women is more adept in generating a VPA-induced thrombocytopenia or those women are more susceptible to VPA-induced bone marrow suppression.…”
Section: Discussionsupporting
confidence: 46%
“…4,5 It is mild to transient in most cases which usually resolves spontaneously on dosage reduction or withdrawal of the drug. 6,7 Available reports showed that thrombocytopenia associated with VPA therapy has been reported to resolve without interruption of VPA treatment 8 and has also been reported to endure over time or to have an erratic course. 5 Reports on the use of VPA with psychiatric patients have described a drop in platelet count without thrombocytopenia or with a minimal incidence of thrombocytopenia 9,10 without any associated adverse clinical events related to this findings.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent retrospective study, 21% (62/306) children on VPA developed thrombocytopenia (defined as platelet count < 150,000); 32 of these had at least one platelet count < 100,000, and 8 developed clinical signs of bleeding (13). Thrombocytopenia was dose-related, especially when the VPA level was over 140 ug/ml.…”
Section: Valproic Acidmentioning
confidence: 96%